PERAN ISTRI NELAYAN DALAM MENINGKATKAN PENDAPATAN KELUARGA - Sudiyarti, Nining; Anjani, Ira (Pusat Riset dan Publikasi, 2024)
This study aims to determine the role of fishermen's wives in increasing family income. The type of this study was associative which aims to examine the effect of fishermen's wife's income (X) on family income (Y). The type of data used in this study was quantitative data collected by researchers directly through interviews with informants related to the research object. The number of samples that will be used as respondents in this study was 100 fishermen's wives in Sumbawa District who were determined using non-probability sampling techniques with the accidental sampling method. All data that has been collected was processed using the SPSS program to be analyzed and interpreted using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination testing (R2). The results of this study showed that the income of fishermen's wives had a positive and significant effect on family income in Sumbawa District. This means that the greater the income earned by the fisherman's wife, the greater the family income will increase. Conversely, the lower the income earned by the fisherman's wife, the greater the family income will decrease. The degree of effect of the fisherman's wife's income variable on family income was 42.9%, while the remaining of 57.1% was effected by other variables outside this research model, such as education level, number of family dependents, working hours, and cost of living.